Visual Effects of Intravitreal Triamcinolone Acetonide Injection in Patients with Refractory Diabetic Macular Edema - Baig, Zaheer ud Din Aqil Qazi, Khalid Mehmood, Baber Attique Malik, Muhammad Tariq Khan Mirza Jamil ud Din (Pakistan Journal of Ophthalmology, 2010)
Purpose: The visual outcome in patients with refractory diabetic macular edema receiving intravitreal triamcinolone acetonide injection. Materials and Methods: This was an interventional, prospective hospital based study conducted at LRBT Eye Hospital Lahore from Jan 2007 to Aug 2007. Fifty eyes of 50 patients received lntravitreal injection of triamcinolone in a single dose of 4mg/0.1 ml. visual acuity was measured preoperatively and at postoperative visit of 1 week, 1 month and 3 months using Snellen’s Visual Acuity chart. Results: Pre operatively there was 1 (2%) eye with VA > 6/18, 28 (56%) eyes with VA 6/24-6/60 and 21 (42%) eyes had VA <6/60. On third post operative month follow up visit day there were 6 (12%) eyes with VA > 6/18, 31 (62%) eyes with VA 6/24-6/60 and 13 (26%) eyes had VA <6/60. There is statistically significant difference between the preoperative and postoperative visual acuity, p=0.005. Conclusion: This study suggests that lntravitreal injection of triamcinolone acetonide in a dose of 4mg/0.1ml considerably improved vision in patients with diffuse diabetic macular edema refractory to previous macular grid photocoagulation at three months after the injection.